PENGARUH BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA KARYAWAN PT. XAB INDUSTRIAL SERVICE DURI - Al Mustaqim, Maulana; Kartikowati, Sri; syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The study aims to determine the influence of organizational cultures on employee work disciplines. The population in this study is all employees of PT. XAB Industrial Service Duri as many as 130 employees. Samples of 57 respondents were taken using Taro Yamane's technique of random sampling. Data is collected using a questionnaire, then analyzed by a simple linear regression method. The results showed the influence of organizational culture to work discipline against employee performance with a donation of 0.292 or 29%. With the equation Y = 10.813 + 0448 X1 This research advice can be used as a reference to improve employees ' performance through the implementation of organizational culture to the work discipline of PT employees. XAB Industrial Service DuriKey Words: Organizational Culture, Work Discipline.